2023
DOI: 10.1002/glia.24471
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte‐like subpopulation of NG2 glia in the adult mouse cortex exhibits characteristics of neural progenitor cells

Lucie Janeckova,
Tomas Knotek,
Jan Kriska
et al.

Abstract: Glial cells expressing neuron‐glial antigen 2 (NG2), also known as oligodendrocyte progenitor cells (OPCs), play a critical role in maintaining brain health. However, their ability to differentiate after ischemic injury is poorly understood. The aim of this study was to investigate the properties and functions of NG2 glia in the ischemic brain. Using transgenic mice, we selectively labeled NG2‐expressing cells and their progeny in both healthy brain and after focal cerebral ischemia (FCI). Using single‐cell RN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 163 publications
2
6
0
Order By: Relevance
“…Although it has been well established that neurons synapse on NG2 cells and have a modulatory role in their development and regeneration, very recently it was revealed that NG2 cells may themselves act as neural progenitor cells. This finding, which was reported in the cortex of adult mouse [245], if verified in human neuronal system, can have a wide implication in providing regenerative interventions in neurodegenerative diseases [245].…”
Section: Nachrs -Ng2 Cellssupporting
confidence: 67%
“…Although it has been well established that neurons synapse on NG2 cells and have a modulatory role in their development and regeneration, very recently it was revealed that NG2 cells may themselves act as neural progenitor cells. This finding, which was reported in the cortex of adult mouse [245], if verified in human neuronal system, can have a wide implication in providing regenerative interventions in neurodegenerative diseases [245].…”
Section: Nachrs -Ng2 Cellssupporting
confidence: 67%
“…Although it was well established that neurons synapse on NG2 cells and have a modulatory role in their development and regeneration, very recently, it was revealed that NG2 cells may themselves act as neural progenitor cells. This finding, which was reported in the cortex of adult mice [245], if verified in the human neuronal system, can have a wide implication in providing regenerative interventions for neurodegenerative diseases [245].…”
Section: Nachrs-ng2 Cellssupporting
confidence: 63%
“…While some NG2-expressing progenitors generate oligodendrocytes throughout life, most of them do not differentiate, and remain proliferative in the cortex 68,130 . A subset of these cells generate protoplasmic astrocytes in the ventral forebrain and spinal cord 66,136 , and a smaller subset has been reported to generate neurons in the piriform cortex 137,138 and dorsolateral cortex 131 .…”
Section: Discussionmentioning
confidence: 99%
“…The broad group of cells often collectively characterized by shared expression of NG2 proteoglycan constitute ~2-3% of neural cells in adult rodent cortex, and are the primary proliferative cell group from early postnatal stages through adulthood and in the aged CNS 123,124 . Recent work reveals that this broad group of "NG2 progenitors" is not a homogeneous population; rather, it consists of at least several subpopulations with distinct molecular, cellular, and functional properties [125][126][127][128][129][130][131][132][133][134][135] . While some NG2-expressing progenitors generate oligodendrocytes throughout life, most of them do not differentiate, and remain proliferative in the cortex 68,130 .…”
Section: Sox6+/ng2+ Progenitors Are a Subset Of Cortical "Ng2 Progeni...mentioning
confidence: 99%